PENGARUH JUMLAH USAHA PENYEDIAAN AKOMODASI DAN USAHA JASA MAKANAN DAN MINUMAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN BADUNG - Chelsea Jashella; I Putu Anom; Putri Kusuma Sanjiwani (CV. Adiba Aisha Amira, 2026)
Bali is known as one of the most popular tourist destinations in the world thanks to its stunning natural beauty and captivating cultural richness. Bali is heavily dependent on the tourism sector. Badung Regency is the regency with the highest regional income in Bali. Badung Regency has the largest number of accommodations and food and beverage service providers in Bali. This study aims to analyse the effect of the number of accommodation businesses and food and beverage service providers on the local revenue of Badung Regency. The data analysis technique used to solve the problems in this study is descriptive quantitative analysis with a secondary data analysis (SDA) approach. The data were analysed using multiple linear regression, t-test, F-test, and coefficient of determination with the help of SPSS. The number of accommodation and food and beverage service providers does not have a simultaneous effect on PHR revenue. The statistical test results show that the number of accommodation providers and the number of food and beverage service providers do not have a significant effect on PHR revenue, with a significance value (X1) of 0.419 (> 0.05) and a significance value (X2) of 0.155 (> 0.05). The statistical test results show that PHR has a significant effect on PAD with a significance value of the PHR revenue variable (X1) of 0.000 (> 0.05), which means that PHR revenue has a significant effect on the rise and fall of PAD.